(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article explores the social psychological characteristics of marital satisfaction in pure and mixed-culture families. It examines how cultural similarities in pure culture families contribute to mutual understanding and shared expectations, while cultural differences in mixed-culture families introduce unique challenges. The article emphasizes the importance of intercultural competence, adaptability, and effective communication in achieving marital satisfaction in mixed-culture families, offering insights into how couples can navigate cultural differences to build strong, satisfying relationships